Hypertension-related distress and its associated factors: findings from an urban primary health centre of South Delhi, India - Anam A. Alwani; Udita Singh; Sujata Sankhyan; Ankit Chandra; Sanjay K. Rai; Baridalyne Nongkynrih (Journal of Family Medicine and Primary Care)
Background: Living with hypertension (HTN) has been found to cause distress, which adversely affects one’s self-care and may lead to elevated blood pressure. There is a paucity of data regarding the prevalence of HTN-related distress. This study was conducted to estimate the prevalence of HTN-related distress among adults with HTN attending an outpatient department in an urban primary health centre and to determine the factors associated with distress. Methods: This was a cross-sectional study conducted at the outpatient department of an urban primary health centre in Delhi, India. The enrolled participants were administered a questionnaire, which included a Distress Scale for patients with diabetes mellitus and/or hypertension (DSDH17 M) (to assess for HTN-related distress) and Health-Related Quality of Life, Healthy Days Measure. A descriptive analysis was performed. Factors associated with HTN-related distress were tested using logistic regression. Results: One hundred forty-one participants were enrolled in this study. Most were women (73.76%) with a mean age of 60.15 years (standard deviation [SD]: 0.78). The prevalence of HTN-related distress (average DSDH17 M score ≥3) was 14% (95% confidence interval [CI]: 9.30–21.03). Patients with HTN-related distress had significantly poor health and reported a greater number of days where they were physically or mentally unhealthy. Patients with uncontrolled blood pressure had six times the odds (95% CI: 1.69–21.77, P value = 0.006) of HTN-related distress compared to those with controlled blood pressure. Conclusions: Hypertension-related distress was present in 14% of adults with HTN. Patients with uncontrolled blood pressure had six times the odds of HTN-related distress.